Bagaimana Satuan Tugas Pencegahan dan Penanganan Kekerasan Seksual (Satgas PPKS) yang ideal? (Peran Psikologi dan Penerapan PPKS di kampus Universitas Udayana Bali) - Swasti Wulanyani Ni Made (Asosiasi Psikologi Forensik (Apsifor), 2022)
Responding the problem of high cases of Sexual Violence in universities, the government through the Ministry of Education, Culture, Research and Technology (Kemenristekdikti) issued Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 30 of 2021 about Prevention and Handling of Sexual Violence in Higher Education (Permendikbudristek No. 30 of 2021). In this regard, the Chancellor of Unud issued the Unud Rector Regulation Number 12 of 2021 concerning Prevention and Handling of Sexual Bullying and Violence (Pertor Unud No. 12 of 2021). Then, the Unud Sexual Violence Prevention and Handling Task Force (Unud PPKS Task Force) was formed based on the Rector's Decree dated December 22, 2021. This task force is temporary because it has not met the established procedures but prevention and handling must be carried out immediately. The Task Force team has fulfilled the elements of lecturers, staff and students and the majority of them are women. The purpose of writing this article is to describe and review the dynamics experienced by the PPKS Unud task force team, which started work since January 2022, so it can be used as lessons for other universities. Dynamics experiences are including handling cases, types of cases, challenges, and the mentoring process that has been provided until September 2022